2019
DOI: 10.1590/s1678-86212019000400350
|View full text |Cite
|
Sign up to set email alerts
|

Painéis de pínus e bagaço de cana empregando-se dois adesivos para uso na construção civil

Abstract: Resumo O presente trabalho objetivou produzir e avaliar painéis aglomerados empregando-se partículas de bagaço de cana-de-açúcar (Saccharum officinarum) e de pínus (Pinus taeda, Pinus elliottii), comparando-se a eficiência de dois adesivos, ureia-formaldeído e poliuretano derivado do óleo de mamona. Os painéis foram preparados com 60% de partículas de pínus e com 40% de partículas de bagaço de cana. Foram avaliadas propriedades físicas (densidade, teor de umidade e inchamento em espessura após 24 h de imersão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
2
1
1
Order By: Relevance
“…Regarding the moisture content, it is noted that the composites manufactured by hot pressing showed higher values than the studies carried out by Buzo et al [28] and Santos et al [29]. However, it is observed that the five treatments (T1, T2, T5, T6, T7) proposed in this study meet the minimum requirements described by the ABNT 14810-1 [30] standard, which presents an acceptance range between 5% and 13%.…”
Section: Resultscontrasting
confidence: 52%
“…Regarding the moisture content, it is noted that the composites manufactured by hot pressing showed higher values than the studies carried out by Buzo et al [28] and Santos et al [29]. However, it is observed that the five treatments (T1, T2, T5, T6, T7) proposed in this study meet the minimum requirements described by the ABNT 14810-1 [30] standard, which presents an acceptance range between 5% and 13%.…”
Section: Resultscontrasting
confidence: 52%
“…No Brasil, para a produção do MDP são utilizadas principalmente madeiras provenientes de florestas plantadas dos gêneros Pinus e Eucalyptus, contudo, a utilização de outros materiais lignocelulósicos pode proporcionar a diminuição de custos sem deixar as atender os requisitos de qualidade. Na literatura, foram citados vários tipos de materiais alternativos com potencial para produção de MDP, dentre os quais: bagaço de cana (BUZO et al, 2019); casca de arroz (SOUZA et al, 2017), casca de amendoim (BARBIRATO, et al, 2014;CRAVO et al, 2015), casca de coco-verde (CRAVO et al, 2015), fibras de bananeira (GUIMARÃES, 2012), resíduos de erva-mate (DE SOUZA et al, 2019) e bambu (BELINI, et al, 2014;ALMEIDA et al, 2008;MELO et al, 2015).…”
Section: Resultsunclassified
“…In the works by Buzo et al [39] and Sugahara et al [40], lower thickness swelling values were also found for particle boards made of PU compared to formaldehyde-based resins. It is also observed that the mean values of swelling in thickness, obtained for all treatments of the present study, are a little below the mean value (7.75%) found in the literature for plywood of Pinus taeda [33].…”
Section: Thickness Swellingmentioning
confidence: 88%